Analgesic Effect of Melatonin in Mice - Mohammad, Imad Hashim (AL-Kindy College Medical Journal, 2012)
Background: Melatonin is the main hormone secreted by the pineal gland. This indole compound (N-acetyl-5-methoxytryptamine) is derived from serotonin after two biochemical steps. Melatonin has been implicated in some pharmacological effects including sedative/hypnotic, anticonvulsant activity and others. The aim of this study was to investigate the antinociceptive effect of different doses of melatonin administered i.p. to mice, and then, to find the dose- response line of melatonin in mice as analgesic agent.Methods: The dose response effect of melatonin (10, 50, and 100mg/kg) were assessed against control using tail flick test in mice as a model of nociceptive pain. In this model, all doses of melatonin were given intraperitoneally 15 min before immersion of tail in hot water 50°C, and Tail Flick Latency was measured before, and after (15, 30, 60 and 120 min ) administration of melatonin.Results: Administration of melatonin i.p. to mice significantly P ≤ 0.05 increase tail flick latency in melatonin treated groups after 30 min and 60 min compared to baseline values; while after 120 min, administration of melatonin produce significant and dose dependent antinociceptive effect following its i.p. administration. The percentage increase in tail flick latency produced by i.p. administration of melatonin doses of 10, 50, and 100 mg/kg were 86.59%, 156.05% and 169.19% respectively when compared to baseline values.Conclusions: The present study showed that melatonin produces analgesic effect in a dose dependent manner in mice, further studies are required to know the exact mechanism by which melatonin exerts this analgesic effect.